Strategy CV Sutejo Motor in Facing the Digital-Based Market - Leksmana, Leo Indra; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives: To analyze how CV strategies. Sutejo Motorcycle is indecisive in facing the digital-based market. Design/method/approach: This study is a qualitative study with a descriptive approach. The data collection method was carried out by interview and observation techniques. Analysis techniques used Data reduction. Research Findings: The results of this study make it easier for business people to enter the market and compete quickly using digital platforms. Some of the themes of the findings include focusing on consulting services to handle customer complaints, Providing the right solutions, Guaranteeing the authenticity of goods, Offering credit facilities, Improving staff training, Cooperating with digital platforms, Expanding market reach, and Developing a delivery system with subscription consumers. Theoretical/Originality Contribution: this research adds or develops a theory about an adaptive marketing strategy. Practice/Policy Implications: Implementing various effective strategies to improve customer service and strengthen its position in the automotive parts industry. The results of this research can be used to help make policies regarding business strategies. Research Limitations: The limitation of this study is the short research time.